Perancangan Aplikasi Visualisasi Database Produksi dengan Metode Agregasi menggunakan Looker Studio dan Google Sheets Berbasis Web Studi Kasus di PT. ANTAM. Tbk - Darmanto, Yusuf; Koryanto, Lucky; Faizah, NM (Journal Innovations Computer Science, 2023)
The development of information technology has substantially changed the industrial landscape, including production data management. PT. ANTAM Tbk., as a mining and metallurgical company, realizes the significance of using technology to optimize operations and make data-based decisions. This research aims to design a production database visualization application by applying the aggregation method via the web-based Looker Studio and Google Sheets platforms. The aggregation method is applied to combine production data spread across various sources into more concise and easily accessible information. Looker Studio was chosen as a tool for designing interactive and informative data visualizations. Integration with Google Sheets provides flexibility in managing and storing production data. Case study at PT. ANTAM Tbk. used as a basis for applying this design concept in a practical context. This research uses a system development design approach to design and implement a production database visualization application. The analysis stage includes identifying user needs and production data characteristics. The design phase involved developing a data aggregation model and visualization interface using Looker Studio. Integration with Google Sheets was implemented at the development stage. The result of this research is a web application that allows users at PT. ANTAM Tbk. to access, analyze, and visualize production data effectively. This application provides information more quickly, accurately, and relevantly, supporting better decision-making based on data. The implications of this research include contributions to the development of information technology solutions that can increase operational efficiency and effectiveness in the mining and metallurgical industries